Implementasi Akses Keterbukaan Informasi Publik Era Digital Pada Perumdam Tirta Berkah Pandeglang - Muchsinin, Muchsinin; Sjafari, Agus; Yulianti, Rina (Kolaborasi : Jurnal Administrasi Publik, 2025)
This study aims to analyze the implementation of public services related to the openness of public information in the digital era through the website at Perumdam Tirta Berkah Pandeglang along with the obstacles faced. This study is a qualitative study whose data comes from primary and secondary data with data collection techniques through literature studies and interviews that are analyzed qualitatively using the Merilee S. Grindle theory approach. The results of the study concluded that, first, the implementation of public services related to the openness of public information at Perumdam Tirta Berkah Pandeglang through the website in general cannot be accessed in full. This can be seen from the results of the monitoring and evaluation which concluded that public services related to the openness of public information at Perumdam are still far from being "informative". Second, the obstacles faced in implementing public services at Perumdam through the website are limited resources, including: limited knowledge and expertise of human resources in the field of information technology, limited budget, and facilities and infrastructure in meeting the demands of openness of public information in the digital era.